Mediação pedagógica entre professoras e aluno com deficiência física e necessidade complexa de comunicação nas atividades escolares - Camalionte, Daniele de Oliveira (2022)
The pedagogical mediation combined with the use of Assistive Technology (AT) and Augmentative and Alternative Communication (AAC) resources will enable the teacher to plan the best strategies to expand the ways of teaching and learning opportunities for students with disabilities. This research concerns the development of school activities of a literacy program inspired by Paulo Freire's method, carried out in the classroom of resources in a Public School located in a municipality in the countryside of the State of São Paulo. It aimed to analyze the pedagogical mediation of two teachers with a student with physical disabilities (PD) and complex communication needs (CCN) during activities carried out in the resource room, in addition, to describing and analyzing the expressive abilities of the student during the pedagogical activities. The participants of this study were: the special education teacher, the researcher, and a student with PD and CCN. The research is configured as a case study of qualitative and quantitative descriptive approaches, and data collection took place through participant observation, being obtained through video recordings, field diary registration and images. The research material was organized after being evaluated by expert judges in Special Education and contains the transcripts of the videos in a temporal sequence of the activities carried out, constituting a single written text. Data analysis was classified into themes and subthemes according to the literature. As a result, it was possible to analyze the pedagogical mediation strategies made by the teachers during the dialogic teaching, being: Comment, Instruction, Instruction with a clue, Open question, Incentive, Question with a clue, Closed question, Articulating model, and to a lesser extent, Syllabation, Description, Command, Clarification, Command with a clue, Corrective Feedback, and Clue. In addition, the study described and analyzed the expressive skills of the student identified during the literacy program, being initially Combined and non-verbal, presenting variation overtime throughout the meetings, according to the intentional actions of the teachers developed in the pedagogical mediation, they favored the student to demonstrate expressive verbal vocal and non-vocal verbal skills as more symbolic forms of communication, when an AT software was made available to the student and AAC (Prancha Fácil) for the development of school activities, showing more independence and autonomy. Although the high and low features technology used have been valuable tools for student communication and learning, more important than the use of TA and AAC resources was the presence and availability of the teachers to prepare themselves for dialogic interaction, welcoming and responding to the messages, respecting, and using together with the student the alternative modalities of communication.